Pinagmat'tan upholding the Nabuenos' tradition of the Soledad with rondalla as a cultural heritage - Ballester, Marie France Vasquez
The purpose of this project is mainly to uphold the town's distinctive tradition of the Soledad Procession's performances with the incorporation of rondalla as the source of the music and moreover as a culturaql heritage itself.